EFFECT OF VARYING OCEANICITY ON EARLY- TO MID-HOLOCENE PALAEOHYDROLOGY, KOLA PENINSULA, RUSSIA: ISOTOPIC EVIDENCE FROM TREELINE LAKES - Wolfe B.B.; Edwards T.W.D.; Jiang H.; MacDonald G.M.; Gervais B.R.; Snyder J.A. (My University, 2003)
The stable-isotope stratigraphy of sedimentary organic matter and algal cellulose in cores from two lakes near treeline on the Kola Peninsula indicate changes in water and nutrient balance that correlate with inferred expansion of Pinus sylvestris during the early to mid-Holocene. Trends in cellulose-inferred lakewater d 18 O values for both lakes suggest that moist conditions after deglaciation were followed by progressive drying from about 9500 to between 8000 and 7500 14 C yr BP. Although pine appeared in the area by 8000 14 C yr BP, the maximum density of trees locally, as suggested by stomate evidence, occurred during subsequent moistening between 7500 and 6000 14 C yr BP. This is c. 1000 years later than in other regions of northern Russia and is possibly attributable to limitations on seedling establishment and survival due to root desiccation during dry winters. Changes in nutrient balance and productivity in the lakes, as inferred from variations in sediment carbon and nitrogen elemental abundances and their respective stable-isotope signatures, are also consistent with expected changes in hydrological and edaphic conditions. Development of moister conditions at about 7000 14 C yr BP on the Kola Peninsula is in harmony with evidence for increased oceanicity at this time in central Siberia, which is thought to ree ect enhanced propagation of warm, moist air masses across northern Eurasia due to increased sea-surface temperatures and reduced sea-ice cover in the Nordic Seas.
Keywords: Isotope palaeohydrology; sedimentary organic matter; lacustrine sediments; carbon and nitrogen cycling; palaeoclimate; algal cellulose; treeline; Russia; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен